The Role of Cultural Education and Training at the DKI Jakarta Pavilion Taman Mini Indonesia Indah in Maintaining Local Wisdom - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Insani, Alisya Nur; Madyaningrum, Ika Ristiyani (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This final report is entitled "The Role of Cultural Training Platforms in Taman Mini Indonesia Indah in Maintaining Local Wisdom". This research is motivated by the role of education and cultural training which is very important and must be disseminated to tourists. DKI Jakarta Pavilions must be able to provide information related to Betawi culture which is still not known externally by tourists and provide good service to tourists. Providing good service and interesting information will create satisfaction and new insights for tourists who enjoy the attractions and culture in Jakarta Beautiful Indonesia Miniature Park Pavilion The purpose of this research is to find out the benefits of DKI Jakarta pavilions and whether there is a role for education and training in DKI Jakarta pavilions. The research method used is qualitative and quantitative, with data collection techniques by observation, interviews, and documentation. The results of this study are tourists' perceptions of the role of education and culture in maintaining local wisdom. Suggestions that can be given to the management of the DKI Jakarta Pavilion in an effort to play a role in cultural education and training are to further improve service quality and improve modern visualization so that tourists are interested in visiting it.